On the Consolidation of Normative Legal Acts in the Russian Federation - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2022)
The scientific article analyzes such a form of systematization of regulatory legal acts in the Russian Federation as their consolidation. Attention is drawn to the problem of the correlation between codification and consolidation of legal acts. It is noted that this form of systematization has a very limited distribution in Russia in comparison with foreign (France, Great Britain, Germany, USA) countries, in which the consolidation of normative legal acts is understood somewhat differently than in Russian legal science.